Non-Invasive Brain Stimulation for the Treatment of Symptoms Following Traumatic Brain Injury - Dhaliwal, Simarjot K.; Meek, Benjamin P.; Modirrousta, Mandana M. (Frontiers in Psychiatry, 2015)
Background Traumatic brain injury (TBI) is a common cause of physical, psychological, and cognitive impairment, but many current treatments for TBI are ineffective or produce adverse side effects. Non-invasive methods of brain stimulation could help ameliorate some common trauma-induced symptoms. Objective This review summarizes instances in which repetitive Transcranial Magnetic Stimulation (rTMS) and transcranial Direct Current Stimulation (tDCS) have been used to treat symptoms following a TBI. A subsequent discussion attempts to determine the value of these methods in light of their potential risks. Methods The research databases of PubMed/MEDLINE and PsycINFO were electronically searched using terms relevant to the use of rTMS and tDCS as a tool to decrease symptoms in the context of rehabilitation post-TBI. Results Eight case-studies and four multi-subject reports using rTMS and six multi-subject studies using tDCS were found. Two instances of seizure are discussed. Conclusion There is evidence that rTMS can be an effective treatment option for some post-TBI symptoms, such as depression, tinnitus, and neglect. Although the safety of this method remains uncertain, the use of rTMS in cases of mild TBI without obvious structural damage may be justified. Evidence on the effectiveness of tDCS is mixed, highlighting the need for additional investigations.